Learning Arabic with Animaker-Based Learning Videos for Elementary School Students - Rahayu Mustika Rafi (Yayasan Adra Karima Hubbi, 2023)
The development of technology in this era means that teachers are increasingly required to create a pleasant learning atmosphere, no longer monotonous by using thick textbooks. The pleasure of learning can certainly make students more interested in the lesson and easily digest the lesson. The aim of this research is to prove that animaker-based learning videos can make learning Arabic fun and also make it easier for teachers in the teaching and learning process. The method used in this research is descriptive qualitative by referring to reliable research. This research found that by using the Animaker application, learning Arabic for elementary school students will not feel difficult and will be more fun because of the interesting videos.